Fair weather friends ; Lampang Kerubin; Unconquerable - Lazaro, Cheche; Mephejanij Phaton Youth Club. (Quezon City Probe Productions, 1991)
Friendship between the Filipinos and Americans in Olongapo City was affected that they refused to allow passage in Subic during the Pinatubo eruptions ; A film about mentally handicapped children and of Randy Zialcita whp played Julius in the film; Mephenaij Pheton Youth Club, a group of youth who choose Apahan, Leyte to improve their community.
Fair weather friends (15 min.) -- Lampang Kerubin (13 min.) -- Unconquerables (12 min.).
VHS.
Reporters, David Celdran, Luchi Cruz-Valdes.
Keywords: Mount Pinatubo (Zambales) -- Eruption, 1991.; Television film -- Production and direction; mentally handicapped children -- Philippines; Youth -- Societies and clubs. -- Philippines -- Apahan (Leyte); Philippines -- Foreign relations -- United States; United States -- Foreign relations -- Philippines